2022
DOI: 10.1155/2022/3482450
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Urinary Tract Infection in Pediatric Patients with Ureteropelvic Junction Obstruction after Primary Unilateral Pyeloplasty

Abstract: Objective. Ureteropelvic junction obstruction (UPJO) represents to a leading cause of fetal hydronephrosis, which is associated with urinary tract infection (UTI) and urinary stone disease. This study is aimed at investigating risk factors of UTI in pediatric patients with UPJO after primary unilateral pyeloplasty. Methods. The records of a consecutive series of patients undergoing primary pyeloplasty at a single institution between June 2015 and November 2021 were retrospectively reviewed. Demographic and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…Our study demonstrated that an ultrasound RCT of less than 3 mm is an independent risk factor for morbidity following pediatric pyeloplasty. Consistent with our results, Wang et al 9 . compared two groups of children who had primary unilateral pyeloplasty according to the presence or absence of UTI postoperatively.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our study demonstrated that an ultrasound RCT of less than 3 mm is an independent risk factor for morbidity following pediatric pyeloplasty. Consistent with our results, Wang et al 9 . compared two groups of children who had primary unilateral pyeloplasty according to the presence or absence of UTI postoperatively.…”
Section: Discussionsupporting
confidence: 91%
“…12 Although Li et al 8 found that renal pelvic APD was predictive of negative outcomes following laparoscopic pyeloplasty in children, most authors did not find an association between hydronephrosis grade and postoperative complications. 6,7,9 Numerous studies have validated the use of renal pelvic APD in predicting surgical indication in children with UPJ obstruction-like hydronephrosis. However, this factor does not appear relevant to postoperative outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results highlighted significant factors: age at surgery, duration of hydronephrosis, weight, and serum creatinine. These align with prior research emphasizing their importance in UPJO surgery [7,[11][12][13]. Unlike most studies focusing on singlefactor analysis, we used comprehensive multivariate logistic regression for a more realistic understanding of UPJO surgical outcomes.…”
Section: Discussionmentioning
confidence: 95%